Praca w grupach jako forma realizacji celów komunikacyjnych i refleksji nad językiem - Janowska, Iwona (Neofilolog, 2012)
Language learning in cooperation is a social and sociocultural dimension of action-based approach. By means of language education the school prepares students to undertake social activities and to cooperate with native language speakers. Therefore, teamwork teaching and learning, team pursuance of mutual goals with the use of foreign language has become one of the priorities of action-based didactics. We usually talk about positive aspects of teamwork in the context of communication teaching. Team cooperation is less frequently perceived as a form of pursuing another goal of language education, i.e. linguistic competence development. Apart from pursuing communicative goals work in small groups lets the learners get involved in explicit work with language structures, observe and discover language rules, test formed hypotheses in texts they create and master their competencies by reflecting on the language. The purpose of the paper is to present organisational forms of classes applied most frequently in foreign language teaching and learning actionbased process.